2010
DOI: 10.1016/j.jasms.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Organic secondary ion mass spectrometry: Signal enhancement by water vapor injection

Abstract: The enhancement of the static secondary ion mass spectrometry (SIMS) signals resulting from the injection, closely to the sample surface, of H 2 O vapor at relatively high-pressure, was investigated for a set of organic materials. While the ion signals are generally improved with increasing H 2 O pressure upon 12 keV Ga ϩ bombardment, a specific enhancement of the protonated ion intensity is clearly demonstrated in each case. For instance, the presence of H 2 O vapor induces an enhancement by one order of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…By injection of water vapor ~1 mm above the target surface at a pressure of ~10 −3 mbar, an order of magnitude enhancement of the ion signal was observed for various amino acids and peptides. [4] Our laboratory has proposed that dynamically created protons formed during depth profiling experiments can provide a path for ion enhancement via [M+H] + formation. [5],[6] Finally, it has recently been demonstrated that direct bombardment of a surface with [H 2 0] 1000 + can lead to more than an order of magnitude enhancement of a variety of molecules, ranging from lipids to peptides to drugs compared with Ar 1000 + bombardment.…”
Section: Introductionmentioning
confidence: 99%
“…By injection of water vapor ~1 mm above the target surface at a pressure of ~10 −3 mbar, an order of magnitude enhancement of the ion signal was observed for various amino acids and peptides. [4] Our laboratory has proposed that dynamically created protons formed during depth profiling experiments can provide a path for ion enhancement via [M+H] + formation. [5],[6] Finally, it has recently been demonstrated that direct bombardment of a surface with [H 2 0] 1000 + can lead to more than an order of magnitude enhancement of a variety of molecules, ranging from lipids to peptides to drugs compared with Ar 1000 + bombardment.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 A method of globally increasing ionisation of secondary species is the current ‘holy grail’ in ToF-SIMS development. The presence of water (and/or ice) on 28 and in the sample has shown varying enhancement for species where ion formation is through proton transfer with experiments reported where water has been squirted onto the sample during analysis 44 . Alternatively developments in laser post ionisation of the neutral portion of the secondary species (>99% of ejected material) have the potential to deliver huge increases in signal if the problem of photon induced fragmentation can be overcome.…”
Section: Conclusion and Future Directionmentioning
confidence: 94%
“…Controlling the sublimation-condensation equilibrium of water on the sample surface during analysis has been shown to enhance ion yields by up to two-fold during depth profiling experiments [93, 94]. Surprisingly, leaking water vapor directly over the sample has also produced significant enhancement of analyte detection [95]. Post-desorption photoionization is another way to generate more detectable ions from the neutral molecules that comprise the vast majority of desorption events [96].…”
Section: Secondary Ion Mass Spectrometry (Sims)mentioning
confidence: 99%